The Moderating Role of Conspicuous Consumption Tendency on the Effect of Love of Money on Investment Intention - YÜCEL, Engin; KARATAŞ YÜCEL, Ezgi; GÜLER ÖZÇALIK, Sevinç (International Journal of Contemporary Economics and Administrative Sciences, 2025)
In today’s consumer societies, money functions not only as an economic resource but also as a psychological and sociocultural symbol, shaping individuals’ attitudes toward both consumption and future-oriented financial behavior. Building on this perspective, the study empirically investigates how these meanings translate into investment-related decisions and how consumption-driven values interact with financial motives. The research was conducted using quantitative design with data collected through an online survey distributed via social media platforms. A convenience sampling method was employed, and the final sample consisted of 421 participants representing diverse demographic backgrounds. The love of money, conspicuous consumption, and investment intention were measured using validated scales widely employed in previous studies. A three-stage regression analysis revealed that love of money has a positive and significant effect on investment intentions. Individuals who perceive money as a source of motivation or wealth are more inclined to invest. However, higher levels of conspicuous consumption weaken this positive relationship, suggesting that status-oriented consumption values may reduce the role of economic rationality in investment decisions. These findings indicate that financial institutions should consider psychological and sociocultural factors when designing investment products. Moreover, financial literacy programs should incorporate socio-cultural dimensions to improve understanding of investor behavior.